Mediated group communication for sustainable entrepreneurship: insights from former Indonesian migrant workers in Lombok - Muksin, Nani Nurani; Purnamasari, Oktaviana; Jumail, (Frontiers in Communication, 2026)
Return migration is often framed as a catalyst for rural development, yet the communicative processes through which reintegration and post-migration entrepreneurship are sustained remain underexplored. This article examines how mediated group communication shapes the reintegration experiences of returned Indonesian migrant workers in Lombok. Drawing on a qualitative case study combining in-depth interviews, focus group discussions, and mediated communication observation of WhatsApp groups and community Facebook pages, the study analyses how returnees organize livelihoods, negotiate participation, and sustain collective action after migration. The findings identify three interrelated communicative mechanisms. First, mediated group communication enables an equalization of voice under cultural constraint, allowing women and less dominant actors to participate more actively while remaining embedded in local hierarchies. Second, group communication functions as institutional substitution, compensating for fragmented and episodic state support by coordinating production, circulating market information, and maintaining collective momentum. Third, affective operational coupling reveals how emotional exchanges such as humour and encouragement are inseparable from organisational routines, reinforcing discipline and entrepreneurial persistence. Together, these mechanisms show that mediated group communication operates not merely as a channel of interaction but as a communicative infrastructure that sustains reintegration as an ongoing social process. By reframing digital and face-to-face communication as constitutive of post-migration entrepreneurship, the study extends theories of computer-mediated communication and group interaction in culturally embedded and institutionally constrained contexts. The findings contribute to communication scholarship by demonstrating how communities in the Global South mobilize communication itself as a form of capital for resilience and collective economic action.